Online Health Information Seeking Behavior and Thriving Quotient: A Cross-Sectional Study among Filipino College Students - Guanco, Rhalf Jayson F.; Castillo, Sheryll Ann M.; Balila, Edwin A. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Accurate and reliable health information is critical for students' ability to thrive and overall well-being during the COVID-19 pandemic. However, research on online health information-seeking behavior and thriving in a non-western country and during a pandemic is scarce. The purpose of this study is to examine the relationship between online health information seeking behavior (OHISB) and the thriving quotient (TQ). The researchers enrolled 830 males and females from randomly selected universities in the Philippines. The self-constructed Online Health Seeking Information Behavior (OHSIB-12) and the modified Thriving Quotient (TQ-30) were used as valid and reliable research instruments. This study revealed that the majority of university students had meager to high levels of TQ subcomponents and an acceptable level of OHSIB. Correlation analyses revealed a positive correlation between online health information seeking behavior and the components of the thriving quotient. Developing a healthy online information search can influence students to make healthier choices, thereby improving their sense of well-being and increasing their chances of thriving in an uncertain world. It was recommended that students receive proper guidance from educational and health authorities regarding their OHSIB. Keywords : thriving quotient, online health information, pandemic